ADHESION OF THIN COATING ON ALUMINUM ALLOYS - Suryanto Suryanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
ADHESION OF THIN COATING ON ALUMINUM ALLOYS. Adhesion of thin coating on aluminum alloy was studied. Adhesion of thin coating on a substrate is a key parameter in surface engineering. Adhesion testing becomes interesting thing to be applied in characterization of a coating, even though the fundamental understanding of the process is still limited. Adhesion evaluation of a coating can be carried out using many methods and one of them is scratch method. Scratch was performed on a surface of coating by means of an indenter. The indenter should be very hard such as a diamond. Scratch was obtained by moving the sample under indenter slowly with a constant speed. A progressive increase or step wise load was given. The scratches were evaluated by means of a scanning electron microscope. In this study, adhesion of metallic coating-copper, nickel, chromium and ceramic coating-titanium nitride, chromium nitride on aluminum alloy and that on nickel deposited aluminum alloy were evaluated. Scratch testing with a step wise load was applied. Three parameters of adhesion-critical load, adhesion index and interface toughness were discussed. The results show that scratch testing is suitable for evaluating the above coating.Adhesion of duplex coating is higher than that of single coating and adhesion of duplex nickel coating is the highest.